2008
DOI: 10.1111/j.1526-4637.2007.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Veterans Affairs Primary Care Clinicians' Attitudes toward Chronic Pain and Correlates of Opioid Prescribing Rates

Abstract: High clinician confidence and interest in treating chronic pain concurrent with low satisfaction with ability to provide optimal treatment suggests a need for more system support. VA primary care clinicians are frequently influenced by fears of contributing to dependence or addiction. The relationships among panel size, job satisfaction, and opioid prescribing rates merit additional investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 24 publications
5
113
0
2
Order By: Relevance
“…1,5,6,22 PCPs frequently expressed frustration and concern in their questions to specialists, a finding that is likewise reflected in the literature. 23,24 One study found that nearly three quarters of PCPs considered providing chronic pain care to be a major source of frustration. 23 In response to these concerns, specialists in our study expressed empathy for PCPs, validating their concerns and reinforcing how challenging it can be to care for patients with chronic pain especially when a solution is elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,5,6,22 PCPs frequently expressed frustration and concern in their questions to specialists, a finding that is likewise reflected in the literature. 23,24 One study found that nearly three quarters of PCPs considered providing chronic pain care to be a major source of frustration. 23 In response to these concerns, specialists in our study expressed empathy for PCPs, validating their concerns and reinforcing how challenging it can be to care for patients with chronic pain especially when a solution is elusive.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 One study found that nearly three quarters of PCPs considered providing chronic pain care to be a major source of frustration. 23 In response to these concerns, specialists in our study expressed empathy for PCPs, validating their concerns and reinforcing how challenging it can be to care for patients with chronic pain especially when a solution is elusive. Specialists also reaffirmed that PCPs are benefiting patients simply by providing a comforting, supportive presence, a claim supported by recent research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most medical settings do not have the type of integrated care necessary to effectively treat patients with chronic pain, and primary care physicians (PCPs) are frequently relied upon for pain management [15]. Physician's beliefs and attitudes, including the perception that they have been inadequately trained to treat patients with chronic pain [16], may lead providers' to be reluctant to prescribe opiates for patients who could benefit from them. Conversely, the patients who are receiving opiates may not be prescribed in an optimally safe and effective manner, as PCPs may not be able to conduct the in-depth biopsychosocial assessment and regular follow-up needed for these patients given the limited time and competing clinical priorities in typical primary care visits.…”
Section: Researchmentioning
confidence: 99%
“…Although specialized multidisciplinary pain treatment is necessary and effective, particularly for more complex patients [8][9], access to these services is limited and is often not needed [7,10]. Thus, while most patients with chronic pain are treated by a primary care provider (PCP), most PCPs face organizational and administrative barriers to providing effective care [11], receive limited training in pain management [12][13], express low confidence in their ability to care for such patients [14][15][16][17], and hold reservations regarding treatment of chronic pain. Studies suggest that there is wide variability in PCPs' adherence to guidelines for pain management [18][19][20], and documentation of comprehensive pain care plans and specific treatment provided is poor [21][22].…”
Section: Introductionmentioning
confidence: 99%